The role of ply angle in interlaminar delamination properties of CFRP laminates. (September 2021) - Yang, Fan; Yi, Fajun; Xie, Weihua
Abstract: The paper describes the fracture toughness of biomimetic architected carbon fiber reinforced polymer (CFRP) laminates via experimental and numerical methods. High-fidelity Finite Element (FE) models in conjunction with modified Mises criteria have been developed to evaluate the effect of the interlaminar architectures on the fracture toughness of bio-inspired helicoidal composites. A bi-linear cohesive zone model (CZM) with Hashin damage criterion has been used here to simulate the interlaminar and intralaminar damage behaviors during quasi-static three-point bending (3 PB) tests of biomimetic architected CFRP laminates, and 3 PB test results extracted from open literature and obtained in this work have been used to validate the load-displacement response of the specimens predicted from the proposed FE model. Mode I and mode II interlaminar fracture toughness of these layered composites have also been identified as semi-analytical functions of the stacking angle of two adjacent layers, and the predictions show a good agreement with the corresponding experimental data. This work provides guidelines about the use of the bionic design CFRP composite in applications where toughness is critical. Highlights: Interlaminar delamination numerical model of CFRP laminates is developed. Analytical expressions to estimate the mode I and mode II interlaminar fracture toughness are established. DCB/ENF tests are performed to predict the interlaminar fracture toughness in various interfaces. Test data extracted from open literature and this work are used to validate the finite element model proposed in this paper.